First record of the megamouth shark Megachasma pelagios (Lamniformes: Megachasmidae), from the United Republic of Tanzania - Beuningen, David Van; Bennett, Rhett H.; Abdulla, Abdalla S. (Zootaxa, 2023)
The megamouth shark Megachasma pelagios (Lamniformes: Megachasmidae) was described in 1976 from a specimen caught off Hawaii (Taylor et al. 1983) and is the only extant member of its family and genus (Diez et al. 2022). From 1976 to 2010 M. pelagios was considered rare, with only 50 individuals recorded globally during that time (Nakaya 2010). In recent years it is apparent that it is more common and widespread than previously thought, with 273 confirmed records to date across 16 countries in the Atlantic, Indian and Pacific Oceans (Yu et al. 2021; Diez et al. 2022; Skelton et al. 2023). This species is classified as Least Concern on the IUCN Red List of Threatened Species, as it is globally distributed and does not appear to be heavily impacted by fisheries (Kyne et al. 2019).